"Patients Included" in the European Respiratory Society International Congress. Issue 4 (December 2015) - Smyth, Dan; Powell, Pippa; Masefield, Sarah
Patient involvement or inclusion in medical and healthcare conferences is currently a hot topic [1]. "Patients Included" [2] is a movement that strives to encourage organisers of health conferences to invite patients to the meetings they hold to discuss issues which affect them and ensure they play an active part in them. Patients are included, welcomed and integrated at the ERS International Congress http://ow.ly/UpV8A